A Contextual Analysis and Logic Model for Integrated Care for Frail Older Adults Living at Home: The INSPIRE Project - Yip, Olivia (Int J Integr Care, 2021)
INTRODUCTION: Implementation science methods and a theory-driven approach can enhance the understanding of whether, how, and why integrated care for frail older adults is successful in practice. In this study, we aimed to perform a contextual analysis, develop a logic model, and select preliminary implementation strategies for an integrated care model in newly created information and advice centers for older adults in Canton Basel-Landschaft, Switzerland. METHODS: We conducted a contextual analysis to determine factors which may influence the integrated care model and implementation strategies needed. A logic model depicting the overall program theory, including inputs, core components, outputs and outcomes, was designed using a deductive approach, and included stakeholders’ feedback and preliminary implementation strategies. RESULTS: Contextual factors were identified (e.g., lack of integrated care regulations, existing community services, and a care pathway needed). Core components of the care model include screening, referral, assessment, care plan creation and coordination, and follow-up. Outcomes included person-centred coordinated care experiences, hospitalization rate and symptom burden, among others. Implementation strategies (e.g., nurse training and co-developing educational materials) were proposed to facilitate care model adoption. CONCLUSION: Contextual understanding and a clear logic model should enhance the potential for successful implementation of the integrated care model.